Biomolecular Piezoelectric Materials: From Amino Acids to Living Tissues. Issue 14 (26th February 2020) - Kim, Daeyeong; Han, Sang A; Kim, Jung Ho; Lee, Ju‐Hyuck; Kim, Sang‐Woo; Lee, Seung‐Wuk
Abstract: Biomolecular piezoelectric materials are considered a strong candidate material for biomedical applications due to their robust piezoelectricity, biocompatibility, and low dielectric property. The electric field has been found to affect tissue development and regeneration, and the piezoelectric properties of biological materials in the human body are known to provide electric fields by pressure. Therefore, great attention has been paid to the understanding of piezoelectricity in biological tissues and its building blocks. The aim herein is to describe the principle of piezoelectricity in biological materials from the very basic building blocks (i.e., amino acids, peptides, proteins, etc.) to highly organized tissues (i.e., bones, skin, etc.). Research progress on the piezoelectricity within various biological materials is summarized, including amino acids, peptides, proteins, and tissues. The mechanisms and origin of piezoelectricity within various biological materials are also covered. Abstract : The piezoelectricity of the various elements constituting the human body has attracted intensive attention, due to the strong piezoelectricity, biocompatibility, low dielectric, and tissue regeneration effects. Research progress in the various biological piezoelectric materials from the basic building blocks to organized tissues are summarized. The mechanisms and origins of piezoelectricity are discussed, and challenges and perspectives for developing biological piezoelectric materials are presented.